The Implementation of Genre-based Approach in Improving Students’ Descriptive Writing Ability Through Sidney Sheldon’s Novel Rage of Angels as Role Models - Ahmad, I (KnE Social Sciences, 2018)
This study is concerned with Genre-Based Approach applied to the students Senior High School. As the prerequisite, the students should master text types proposed by Derewianka (2003) such as narrative, descriptive, recount, procedure, report, explanation, discussion, exposition, news item and review. The goal of this research is to improve students’ ability to write descriptive writing by applying the theory. Teachers tried to find out a solution by having a classroom action research (CAR) for them. The theory of CAR was proposed by Berg (2004). This research only focused on Descriptive text using Sidney Sheldon’s novel Rage of Angels as the role models. There are two statements of the problem of this research: Do the role models of Descriptive text in the novel improved students writing ability? And how does The Genre-Based Approach improve students’ Descriptive writing ability? This article used qualitative research by giving some tests and questioners to the students. The result of the research showed that the implementation of Genre-Based Approach significantly improves students writing ability. The students writing skill also increased after they tried to learn the novel as a role model to understand Descriptive text. They became more confident and enthusiastic in writing practice. The approach and the novel were the good tools to have a successful target for the students writing ability. Keywords: Genre-Based Approaches, descriptive texts, writing skills, role models.